Infark Miokard di Indonesia: Tinjauan Literatur Terbaru terhadap Faktor Risiko, Karakteristik Klinis, Manajemen Keperawatan, dan Prediktor Prognostik - Lutfillah Asshidiq; Wisudawan, Wisudawan; Theo Deus (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Acute myocardial infarction is a leading cause of death both in Indonesia and globally, with incidence rates remaining quite high. This disease is closely associated with various modifiable risk factors, including hypertension, diabetes mellitus, dyslipidemia, obesity, and smoking. Various literature reviews confirm that patients with myocardial infarction often have complex clinical conditions, especially when comorbidities worsen the prognosis and increase the burden on healthcare services. This study reviews the latest national literature on risk factors, clinical profiles, nursing management, prognostic predictors, and non-pharmacological interventions such as relaxation techniques. The analysis demonstrates the need for a comprehensive and integrative approach to the management of myocardial infarction patients. This includes early detection using clinical risk scores, intensive nursing interventions in severe cases such as Killip III NSTEMI, and the use of simple prognostic tools that are easily implemented in healthcare facilities. A supportive approach also plays a crucial role in improving patient comfort and adherence to therapy. The integration of these strategies is expected to improve clinical outcomes, reduce morbidity and mortality, and enhance patients' overall quality of life. This study emphasizes the importance of updating local evidence-based clinical practices tailored to the needs of the Indonesian healthcare system, so that the management of myocardial infarction does not only focus on medical therapy, but also on aspects of prevention, non-pharmacological interventions, and ongoing care.